2012
DOI: 10.1097/aln.0b013e31825b57c9
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent Role of Microvascular Endothelial and Polymorphonuclear Cells in Lipopolysaccharide-induced Acute Kidney Injury

Abstract: Ang-2 is increased in older mice, which might cause priming of the endothelial cells. Endothelium responded by a more extensive increase in expression of P- and E-selectin in older mice and increased polymorphonuclear cell influx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…In the previously mentioned studies, inhibiting TLR4 signalling or depleting leucocytes improved renal function. Other data support the opposite scenario where PMN depleted mice subjected to LPS displayed greater kidney injury compared to mice with normal PMN count (Wulfert et al 2012). Several groups have studied the significance of local renal or systemic TLR4 in leucocyte infiltration and renal dysfunction.…”
Section: Leucocyte Infiltration Tlr4 and Si-akimentioning
confidence: 94%
See 1 more Smart Citation
“…In the previously mentioned studies, inhibiting TLR4 signalling or depleting leucocytes improved renal function. Other data support the opposite scenario where PMN depleted mice subjected to LPS displayed greater kidney injury compared to mice with normal PMN count (Wulfert et al 2012). Several groups have studied the significance of local renal or systemic TLR4 in leucocyte infiltration and renal dysfunction.…”
Section: Leucocyte Infiltration Tlr4 and Si-akimentioning
confidence: 94%
“…Other data support the opposite scenario where PMN depleted mice subjected to LPS displayed greater kidney injury compared to mice with normal PMN count (Wulfert et al . ).…”
Section: Leucocyte Infiltration Tlr4 and Si‐akimentioning
confidence: 97%
“…In addition to changes in their life span, neutrophil recruitment is altered with advanced age and after alcohol consumption. Some groups have reported that, with advanced age, neutrophil recruitment to the site of inflammation or infection was reduced or delayed, which was not due to lessened neutrophil chemoattractant levels [102][103][104][105][106][107]; yet, other studies showed heightened neutrophil recruitment in aged mice compared with young mice, possibly because of higher levels of cellular-adhesion molecules present on the endothelial cells that neutrophils transverse to migrate from the circulation into tissues [108][109][110][111]. The directed migration of neutrophils is compromised with advanced age both in vitro and in vivo, likely because of perturbations in signal transduction [104,112].…”
Section: Neutrophilsmentioning
confidence: 99%
“…Endothelial activation can be represented by elevated levels of circulating sE-selectin, sVCAM-1, and sICAM-1 in the blood of patients with sepsis (6) and after CPB (7Y10). The proinflammatory endothelial activation leads to recruitment of polymorphonuclear leukocytes (PMNs) into organs (11), where they become activated and release cytotoxic enzymes, including elastase and myeloperoxidase (MPO). Elevated levels of these enzymes in the blood indicate that the use of CPB during CABG results in activation of PMNs (12).…”
Section: Introductionmentioning
confidence: 99%